5
\begin{align*}
        &\textit{One can see that:}\\
        &\langle n,x_i\rangle=0\\
        \implies &\partial_k\langle n, x_i\rangle=\langle n_k,x_i\rangle+\langle n,x_{i,k}\rangle=0\\
        \implies &\langle -n_k,x_i\rangle=\langle n_k,x_{i,k}\rangle\\
        \implies &\langle -n_k,x_i\rangle g^{i,j}x_j=\langle n_k,x_{i,k}\rangle g^{i,j}x_j\\
        \textit{Looking at the left expression, one can use:}\\
        &n_k=\alpha^l x_l\implies \langle x_i,n_k\rangle=\alpha^l \langle x_i,x_l\rangle=\alpha^l g_{i,l}\\
        \implies &\alpha^l=\langle x_i,n_k\rangle g^{i,l}\\
        \textit{Plugging this into the left expression and adapting the indices:}\\
        \implies -n_k=...
        \end{align*}

enter image description here

2
  • Welcome to TeX.SE! Please make your code snippet be compilable, then we do not have to guess what you are doing ...
    – Mensch
    Mar 4 at 9:32
  • Sorry, will definitely do that next time:) Mar 4 at 9:41

2 Answers 2

8

The alignment is messed up by the intermittent phrases. Use \intertext to add explanations.

Or, for a more compact spacing, use \shortintertext as @egreg points out in the comments (requires \usepackage{mathtools} instead of \usepackage{amsmath}).

\intertext (package amsmath):

enter image description here

\documentclass{article}
\usepackage{amsmath}
\usepackage{lipsum} % only for demo
\begin{document}
\lipsum[1]

One can see that:
\begin{align*}
        &\langle n,x_i\rangle=0\\
        \implies &\partial_k\langle n, x_i\rangle=\langle n_k,x_i\rangle+\langle n,x_{i,k}\rangle=0\\
        \implies &\langle -n_k,x_i\rangle=\langle n_k,x_{i,k}\rangle\\
  \implies &\langle -n_k,x_i\rangle g^{i,j}x_j=\langle n_k,x_{i,k}\rangle g^{i,j}x_j\\
  \intertext{Looking at the left expression, one can use:}
        &n_k=\alpha^l x_l\implies \langle x_i,n_k\rangle=\alpha^l \langle x_i,x_l\rangle=\alpha^l g_{i,l}\\
  \implies &\alpha^l=\langle x_i,n_k\rangle g^{i,l}\\
  \intertext{Plugging this into the left expression and adapting the indices:}
        \implies & -n_k=...
\end{align*}
\lipsum[2]

\end{document}

\shortintertext (package mathtools):

enter image description here

\documentclass{article}
\usepackage{mathtools}
\usepackage{lipsum} % only for demo
\begin{document}
\lipsum[1]

One can see that:
\begin{align*}
        &\langle n,x_i\rangle=0\\
        \implies &\partial_k\langle n, x_i\rangle=\langle n_k,x_i\rangle+\langle n,x_{i,k}\rangle=0\\
        \implies &\langle -n_k,x_i\rangle=\langle n_k,x_{i,k}\rangle\\
  \implies &\langle -n_k,x_i\rangle g^{i,j}x_j=\langle n_k,x_{i,k}\rangle g^{i,j}x_j\\
  \shortintertext{Looking at the left expression, one can use:}
        &n_k=\alpha^l x_l\implies \langle x_i,n_k\rangle=\alpha^l \langle x_i,x_l\rangle=\alpha^l g_{i,l}\\
  \implies &\alpha^l=\langle x_i,n_k\rangle g^{i,l}\\
  \shortintertext{Plugging this into the left expression and adapting the indices:}
        \implies & -n_k=...
\end{align*}
\lipsum[2]

\end{document}
4
  • 1
    Or, possibly, \shortintertext (requires mathtools).
    – egreg
    Mar 4 at 9:39
  • Thanks a lot, really appreciate the help! Works perfectly now.:))) Mar 4 at 9:41
  • @egreg Thanks, I've added your suggestion to the answer.
    – gernot
    Mar 4 at 9:45
  • 1
    I probably would not use \shortintertext here as the texts are long.
    – daleif
    Mar 4 at 9:45
3

In addition to using \intertext for the two explanatory passages, I would shift the & alignment points from left-alignment to alignment on the = symbols. In fact, you may want to simply drop all \implies directives as they would appear to be implied [pun intended].

enter image description here

\documentclass{article}
\usepackage{mathtools} % for '\DeclarePairedDelimiter' macro
\DeclarePairedDelimiter\iprod\langle\rangle % "inner product"

\begin{document}

One can see that:
\begin{align*}
    \iprod{n,x_i} &=0\\
    \implies \partial_k\iprod{n, x_i}
       &=\iprod{n_k,x_i}+\iprod{n,x_{i,k}}=0\\
    \implies \iprod{-n_k,x_i}
       &=\iprod{n_k,x_{i,k}}\\
    \implies \iprod{-n_k,x_i} g^{i,j}x_j
       &=\iprod{n_k,x_{i,k}} g^{i,j}x_j\\
\intertext{Looking at the LHS expression, one can use:}
    n_k&=\alpha^l x_l \\
    \implies \iprod{x_i,n_k}
       &=\alpha^l \iprod{x_i,x_l}=\alpha^l g_{i,l}\\
    \implies \alpha^l
       &=\iprod{x_i,n_k} g^{i,l}\\
\intertext{Plugging this into the LHS expression and adapting the indices:}
    \implies -n_k &=\dots
\end{align*}

\end{document}
1
  • 1
    Will definitely consider dropping them, thanks for the help!:)) Mar 5 at 11:08

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .